2006
DOI: 10.1159/000090945
|View full text |Cite
|
Sign up to set email alerts
|

Serum Starvation and Growth Factor Receptor Expression in Vascular Smooth Muscle Cells

Abstract: Background: Smooth muscle cell (SMC) proliferation in atherosclerosis is regulated through the interaction of growth factors like platelet-derived growth factor-BB (PDGF-BB) and insulin-like growth factor-1 (IGF-1) and their receptors (R). We hypothesized that serum starvation of SMCs may affect PDGFβ-R and IGF-1-R expression and, consequently, the effect of their cognate ligands on SMC survival/proliferation. Methods and Results: Serum starvation significantly increases PDGFβ-R but not IGF-1-R mRNA and protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…PDGF-BB, which promotes development of the proliferative VSMC phenotype, is a robust inducer of autophagy (118). These results clearly contrast with the observation that both serum starvation and nutrient deprivation, standard inducers of autophagy, inhibit VSMC proliferation (119,120). Moreover, treatment of VSMC with the cortisone reductase inhibitor emodin induces growth arrest and cell death by autophagy (121).…”
Section: Autophagy In Vascular Remodelingmentioning
confidence: 90%
“…PDGF-BB, which promotes development of the proliferative VSMC phenotype, is a robust inducer of autophagy (118). These results clearly contrast with the observation that both serum starvation and nutrient deprivation, standard inducers of autophagy, inhibit VSMC proliferation (119,120). Moreover, treatment of VSMC with the cortisone reductase inhibitor emodin induces growth arrest and cell death by autophagy (121).…”
Section: Autophagy In Vascular Remodelingmentioning
confidence: 90%
“…Additionally, we observed that the mitogenic response to these growth factors was partially dependent on the presence of serum. Observations from other groups which demonstrated altered PDGF receptor expression in cells cultured in the absence of serum factors may offer an explanation for these results 30. Second, the replicability of these results in other cell types, as well as to other species should be a consideration before application in other animal or human studies.…”
Section: Discussionmentioning
confidence: 79%
“…Observations from other groups which demonstrated altered PDGF receptor expression in cells cultured in the absence of serum factors may offer an explanation for these results. 30 Second, the replicability of these results in other cell types, as well as to other species should be a consideration before application in other animal or human studies. Finally, while fibrin is a commonly used hydrogel in tissue engineering for many applications, the possibility that these responses are specific to fibrin compared to other extracellular matrices should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Leptin-induced platelet activity required activation of a signaling cascade that included the long form of the leptin receptor, three kinases of JAK2, PI3K and PKB/Akt, IRS-1, and PDE3A. In addition, smooth muscle cell (SMC) proliferation in atherosclerosis was found [32] to mediate through the interaction of growth factors like platelet-derived growth factor-RB (PDGF-RB) and insulin-like growth factor-1 (IGF-1) and their receptors (R).…”
Section: Resultsmentioning
confidence: 99%